Temperature Fields Induced by Low Power Focused Ultrasound in Soft Tissues During Gene Therapy. Numerical Predictions and Experimental Results - Barbara GAMBIN; Tamara KUJAWSKA; Eleonora KRUGLENKO; Andrzej MIZERA; Andrzej NOWICKI (Archives of Acoustics, 2014)
The aim of this work is twofold. Firstly, to verify a theoretical model which is capable of predicting temperature fields appearing in soft tissues during their ultrasound treatment. Secondly, to analyze some aspects of the dynamics of Heat Shock Response induced by the heating process in the context of therapeutic treatment. The theoretical investigations and quantitive analysis of temperature increments at any field point versus time of heating process, depending on the heat source power, spatial distribution and duration as well as on the tissue thermal properties, has been carried out by Finite Element Method (FEM). The validation of the numerical model has been performed by comparison of the calculation results with the experimental data obtained by measuring in vitro of the 3D temperature increments induced in samples of the turkey and veal liver by the circular focused transducer with the diameter of 15mm, focal length of 25mm and resonance frequency of 2MHz. Various ultrasonic regimes were considered. They were controlled by adjusting ultrasound power and exposure time. The heat shock proteins (HSP) and misfolded proteins (MFP) levels during the proposed cyclic sonification are presented.